Fresh Up Bakery / Mohamad Amirul Azwan Rusli … [et al.]. - Rusli, Mohamad Amirul Azwan; Mohd Nizar, Nor Syazwani; Mohd Daud, Nur Diyanah Fathiah; Yuzaidi, Nurul Asyikin; Zulfika, Syakira Aliah
Fresh Up Bakery is a bakery with a motto of ‘freshly baked with love’. We stand true to our motto with the vision to leave an impact on every customer we serve by delivering high-quality products that are crafted with care, innovation and a commitment. Fresh Up Bakery’s main objective is to establish a bakery with affordable prices, with the hope that everyone has the chance to taste good pastries within their own budget. Whether it is a morning pastry, an afternoon pick-me-up, or a special occasion cake, Fresh Up Bakery is destined to become a beloved destination for those with a penchant for exceptional baked goods. Our bakery consists of a partnership between 5 leaders with significant positions, Mohamad Amirul Azwan as the general manager, Nur Diyanah Fathiah as the administration manager, Nurul Asyikin as the marketing manager, Syakira Aliah as the operation manager and Nor Syazwani as the financial manager. Each manager has to manage specific tasks to make sure the business is running smoothly without any inconvenience coming from any party. Fresh Up bakery is located at No 48, Jalan Plumbum R7/R, Seksyen 7, 40000 Shah Alam, Selangor. Even though we are surrounded by a lot of competitions we believe that our pastries will stand out since we are confident with our capabilities. The main target of Fresh Up Bakery would be adults between the age of 25 - 45 years old. Since we provide a delivery service we believe it will attract more people to try out our fresh pastries. All in all we hope everyone gets to enjoy our baked goods and leave with a happy stomach.